(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the effectiveness of the strategic management of the enterprise, the factor affecting the dog, the issues of improving the competitiveness of the enterprise and the increasing metho in the organization and economic management mechanism.